인공지능 기술과 유료방송 미디어 규제에 대한 도전 - 홍대식(Dae-Sik Hong) (언론정보연구, 2020)
양면 플랫폼으로서의 OTT 동영상서비스 제공자는 데이터 주도 경제 시대에 서비스 패러다임을 완전히 바꿀 수 있는 혁신적인 경쟁 수단을 갖추고 새로운 시장을 창출하고 있다. 특히 동영상서비스에 인공지능 기술을 적용한 사업혁신의 성과는 눈부시다. 이런 상황에서 방송사업을 네트워크-서비스 일체형으로 정의하여 수직적 규제체계의 덫에 갇혀 있는 기존 유료방송 미디어 규제의 적용을 받는 다채널 유료방송사업자는 돌파구를 찾지 못하고 있다. 이런 배경 하에, 이 연구는 인공지능 기술의 미디어 산업에 대한 영향력이 파괴적임에도 OTT 동영상서비스에 비하여 기존 다채널 유료방송의 대응이 미흡한 원인을 유료방송 미디어 규제의 제약에서 찾고 제도적 개선의 당위성과 방향성을 제시하는 탐색적 연구의 성격을 띤다. 이 글은 먼저 OTT 동영상서비스 중 특히 인공지능 기술을 적용한 사업혁신의 전개 상황을 살펴본다. OTT 동영상서비스를 제공하는 온라인 플랫폼 사업자는 양면 플랫폼 사업의 장점인 네트워크 효과를 활용하는 다양한 사업모델을 적용할 수 있는 지위에 있다. 온라인 미디어 플랫폼은 인공지능 기술을 활발하게 도입하고 있는데, 이는 사업모델의 유형과 밀접한 관련을 갖는다. 인공지능 기술 적용의 관점에서 볼 때, 기존 유료방송 미디어 규제는 양면 플랫폼의 성격을 갖고 있는 다채널 유료방송 사업자가 사업모델 기반 경쟁을 제대로 수행할 수 없도록 하는 제도적 장애요인이 되어 인공지능 기술 적용의 유인과 능력을 저해할 수 있다. 이는 사업모델의 제도적 고착화로 표현된다. 기술적인 측면과 영업 방식의 측면에서 이는 다채널 유료방송사업자가 제도적으로 정한 경로에 따라 서비스를 제공하고 제도에서 허용한 범위 내에서만 수익성을 추구할 수 있도록 제약함으로써 다채널 유료방송사업자가 사업모델을 전략적으로 선택할 여지를 좁히고 있다. 그로 인하여 다채널 유료방송사업자와 온라인 미디어 플랫폼과의 경쟁력 격차가 심화하고 있으므로, 기술적인 측면과 영업 방식의 측면에서 제도적 개선이 시급하다. OTT video service providers as a two-sided platform are creating new markets with innovative competitive means to completely change the service paradigm in the era of data-driven economy. In particular, the outcomes of business innovation applying artificial intelligence(AI) technology to video services are remarkable. In this situation, multichannel pay broadcasting operators who are subject to the existing pay broadcasting media regulations which defines broadcasting business as a network-service all-in-one type, thus being trapped in the vertical regulation system, are not finding a breakthrough. Against this background, This study is an exploratory study that finds the reason why existing multichannel pay broadcasting operators respond insufficiently to AI technology despite its destructive influence on the media industry under the constraints of pay broadcasting media regulation and suggests the justification and direction of institutional improvement. This article first looks at the development of business innovations among OTT video services which in particular apply AI technology. Online platform operators that provide OTT video services are in a position to apply various business models that utilize the network effect, which is an advantage of the two-sided platform business. Online media platforms are actively introducing AI technology, which is closely related to the type of business model. From the perspective of applying AI technology, the existing pay broadcasting media regulation becomes an institutional obstacle that prevents multichannel pay broadcasting operators with the characteristics of two-sided platforms from properly performing business model-based competition, thereby impeding the incentive and ability to apply AI technology. This is expressed as the institutional persistence of the business model. In terms of technical aspects and business methods, it is narrowing the room for multichannel pay broadcasting operators to strategically choose a business model by restricting them to provide services in accordance with the institutional path and pursue profitability only within the limits allowed by the institution. As the competitive gap between multichannel pay broadcasting and online media platforms is widening consequently, institutional improvement is urgently needed in terms of both aspects of technology and business methods. KCI Citation Count: 1